Studies on the hemocompatibility of bacterial cellulose - Andrade, Fábia K. (2011)
Among the strategies to improve a material’s hemocompatibility, pre-coating with the tripeptide Arg-Gly-Asp (RGD) is used to favor endothelialization thus lowering thrombogenicity. The blood compatibility of native and RGD-modified bacterial cellulose (BC) was studied in this work for the first time. The plasma recalcification time and whole blood clotting results demonstrate the hemocompatibility of BC. A significant amount of plasma protein adsorb to BC fibres, however, according to analysis by intrinsic tryptophan fluorescence techniques when albumin, c-globulin, and fibrinogen from pure protein solutions adsorb to BC do not undergo detectable conformational modifications. Human microvascular endothelial cells cultured on RGD-modified BC readily form a confluent cell layer, inhibiting the adhesion of platelets. As a general conclusion, both native and RGD-modified BCs may be classified as hemocompatible materials.